Remote workers’ free associations with working from home during the COVID-19 pandemic in Austria: The interaction between children and gender - Hartner-Tiefenthaler, Martina; Zedlacher, Eva; el Sehity, Tarek Josef (Frontiers in Psychology, 2022)
Empirical evidence from the pandemic shows that women carried the major burden of additional housework in families. In a mixed-methods study, we investigate female and male remote workers’ experiences of working from home (WFH) during the pandemic. We used the free association technique to uncover remote workers’ representations about WFH (i.e., workers’ reflection of subjective experiences). Based on a sample of 283 Austrian remote workers cohabitating with their intimate partners our findings revealed that in line with traditional social roles, men and women in parent roles are likely to experience WFH differently: Mothers’ representations about WFH emphasize perceived incompatibility between the work and nonwork sphere whereas fathers’ representations highlight work-family facilitation of WFH. However, gender differences were also prevalent for women and men without children: Women seem to particularly benefit from more concentration at home, whereas men consider WFH as more efficient, practical and leading to less work. Thus, our findings imply that gender affected perceptions of WFH during the pandemic independently from children, but children seemed to increase the existing burden, in particular for women. To conclude, WFH can generally be seen as an enabler to reduce work-life/family conflict for both women and men, but bears different challenges based on the contextual (family) situation.